2004
DOI: 10.1590/s0100-879x2004001200003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of hepatitis A virus isolates in Rio de Janeiro: implications for the vaccination of school children

Abstract: The epidemiology of hepatitis A virus (HAV) infection is shifting from high to intermediate endemicity in Brazil, resulting in increased numbers of susceptible individuals and a greater potential for the emergence of outbreaks. Universal vaccination against HAV has been recommended for children, but updated sero-epidemiological data are necessary to analyze the level of natural immunity and to identify candidates for preventive measures. In addition, more molecular studies are necessary to characterize the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
4
23
2
1
Order By: Relevance
“…HAV RNA was detected in 54.5% of the fecal samples, which is consistent with the results of other studies (Skinhoj et al 1981, Yotsuyanagi et al 1996, Villar et al 2004. On the other hand, it was observed that this rate was significantly greater considering serum samples.…”
Section: Discussionsupporting
confidence: 92%
“…HAV RNA was detected in 54.5% of the fecal samples, which is consistent with the results of other studies (Skinhoj et al 1981, Yotsuyanagi et al 1996, Villar et al 2004. On the other hand, it was observed that this rate was significantly greater considering serum samples.…”
Section: Discussionsupporting
confidence: 92%
“…Using molecular analysis, we detected the co-circulation of subgenotypes IA and IB, which corroborates the findings of other studies conducted in Rio de Janeiro , Villar et al 2004. The co-circulation of two subgenotypes suggests the existence of more than one source of infection.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalent human strains fall into genotypes I or III, each of which are divided into subtypes A and B. In Brazil, co-circulation of subgenotypes IA and IB have been found in Rio de Janeiro , Villar et al 2004. Circulation of subgenotype IA has also been detected in other regions of Brazil (de Paula et al 2004).…”
Section: Of the Individuals Tested Acute Hav Infection In Children Wmentioning
confidence: 99%
“…This demonstrates that a genotype I infection has an endemic character in Brazil, although it is the only South American country in which the circulation of both subgenotypes IA and IB has been reported (de Paula et al 2002, Devalle et al 2003, Villar et al 2004. However, this study differs from that of de , in which the analysis of the nucleotide sequence of the VP1/2A junction region showed the occurrence of only subgenotype IA in isolates from the state of Goiás.…”
Section: Discussioncontrasting
confidence: 61%
“…In Brazil, the only genotype that has been found is genotype I, especially subgenotype IA ). However, subgenotype IB has also been observed to circulate in the states of Rio de Janeiro and Pernambuco and in the Amazon region (de Paula et al 2002, Devalle et al 2003, Villar et al 2004.…”
mentioning
confidence: 99%